Colonization of limestone grasslands by woody plants: the role of seed limitation and herbivory by vertebrates. (7th August 2012) - Laborde, J.; Thompson, K.
Abstract: Questions: Why are some woody species able to colonize open grassland while others are not? How important are seed limitation and grazing by vertebrates for the colonization of grasslands by woody species? What are the effects of the grassland turf on seedling emergence, growth and survival? How frequently are seedlings killed by grazers, and how different are woody species in their resistance to herbivory? Location: Limestone grassland of Cressbrook Dale, Derbyshire, in the Peak District National Park, UK Methods: The emergence, growth and survival of the seedlings of eight scrub species were evaluated using sheep exclosures and paired open plots in the grassland. The grassland turf was clipped in half the area of each plot, to determine the effect on seedling establishment. Seeds of the selected species were sown in the field during autumn 2001 and followed through spring 2004. Results: Dense grassland turf reduces the germination of some woody species and also slows growth of all seedlings. Seeds germinate better in short turf and, having germinated, the most important factor for seedling survival is resistance to browsing, which varies widely among species. The two most successful colonizers – Corylus avellana and Crataegus monogyna – have different routes to establishment. Corylus has very successful seed dispersal and is moderately resistant to herbivory. Crataegus is less successful in dispersal but its seedlings are very resistant to browsing. Other species, such as Prunus spinosa, are as resistant to browsing as Crataegus, but are limited by seed availability. Conclusions: Grazing by vertebrates exerts a dual control on scrub invasion. Livestock maintains a dense, compact turf that interferes with the seed germination and seedling growth of woody plants. Grazing also gives rise to differential survival of woody species as a function of their ability to resist browsing. The density and composition of the heterogeneous patchwork of developing scrub vary continually in accordance with the differential success of species in seed dispersal into the open grassland and the mortality of woody seedlings caused by the temporal and spatial variability of grazing. Abstract : In a factorial field experiment in limestone grassland, we found that grazing by vertebrates exerts a dual control on scrub invasion. Livestock maintains a dense, compact turf that interferes with the seed germination and seedling growth of woody plants. Grazing also gives rise to differential survival of woody species as a function of their ability to resist browsing.